Research of Data Migration from OLTP to OLAP Database Loading Speed - Jankauskas, Robertas; Šešok, Dmitrij (Jaunųjų mokslininkų darbai, 2017)
Data sinchronization between multiple systems is one of the most occuring events when there is a requirement to analyze data to make decisions from which could be made conclusions about activities of organisations. In this work ETL process between Oracle and Microsoft SQL Server database management systems is analyzed using different ETL methodologies and system‘s provided technologies.
Keywords: ETL; data warehouse; Oracle; Microsoft SQL Server; SSIS; DBMS